Control processes in short-term storage: Retrieval strategies in immediate recall depend upon the number of words to be recalled. - Ward, Geoff; Tan, Lydia (Memory & Cognition, 2019)
According to the Atkinson and Shiffrin (1968) model, control processes in the short-term memory store determine the selection of different storage, search, and retrieval strategies. Although rehearsal is the most studied short-term control process, it is necessary to specify the different retrieval strategies available for participants to use in searching for and outputting from short-term or immediate memory, as well as the degree to which participants can flexibly select different retrieval strategies for recalling rehearsed and unrehearsed materials. In three experiments we examined retrieval strategies in tests of immediate free recall (Exp. 1), immediate serial recall (ISR; Exp. 2), and a variant of ISR that we call ISR-free (Exp. 3). In each experiment, participants were presented with very short lists of four, five, or six words and were instructed to recall one, two, three, or all of the items from each list. Neither the list length nor the number of to-be-recalled items was known in advance. The serial position of the first item recalled in all three tasks depended on the number of to-be-recalled items. When only one or two items were to be recalled, participants tended to initiate recall with the final or penultimate list item, respectively; when participants were required to recall as many list items as possible, they tended to initiate recall with the first list item. These findings show that different retrieval strategies exist for rapidly searching for different numbers of items from immediate memory, and they confirm that participants have some control over their output order, as measured by the first items recalled.